Greenhouse Gas Emission Accounting Disclosure, Corporate Characteristics and Governance: An Empirical Investigation on Indonesian Firms - Ratmono, Dwi; Darsono, Darsono; Cahyonowati, Nur; Chaerun Niza, Triana (International Journal of Energy Economics and Policy, 2022)
Currently the world is facing global warming, one of the causes of which is greenhouse gas (GHG) emissions. For these reasons, the disclosure of GHG emission information is one of the interesting research areas. However, previous research generally focused on developed countries with inconsistent findings. In this sense, this study aims to contribute to GHG disclosure by analyzing the characteristics of firms as determinants of GHG emission disclosure in a developing country, Indonesia. This study also analyzed the role of corporate governance consisting of the structure of the board of commissioners and the effectiveness of the audit committee in moderating the effect of corporate characteristics on GHG emission disclosure. The sample consisted of 69 firms-years companies listed on the Indonesia Stock Exchange (IDX). The results of testing with Partial Least Squares-Structural Equation Modeling (PLS-SEM) showed that the structure of the board of commissioners; consisting of indicators of independence, women representation, and the number of members of the board of commissioners; strengthened the leverage effect on GHG emission disclosure. The results of the moderation test also showed that the effectiveness of the audit committee can encourage firms with high leverage and poor performance to reveal more GHG emissions.